Efficient multi-allelic genome editing via CRISPR–Cas9 ribonucleoprotein-based delivery to Brassica napus mesophyll protoplasts - Sahab, Sareena; Runa, Fatima; Ponnampalam, Mahilini; Kay, Pippa T.; Jaya, Elizabeth; Viduka, Katerina; Panter, Stephen; Tibbits, Josquin; Hayden, Matthew J. (Frontiers in Plant Science, 2024)
Canola (Brassica napus L.) is a valuable oilseed crop worldwide. However, trait improvement by breeding has been limited by its low genetic diversity and polyploid genetics. Whilst offering many potential benefits, the application of transgenic technology is challenged by the stringent and expensive regulatory processes associated with the commercialisation of genetically modified organisms, coupled with a prevailing low public acceptance of such modifications. DNA-free genome editing using CRISPR-Cas9 ribonucleoproteins (RNPs) offers a promising way to achieve trait improvements without the limitations of transgenic methods. Here, we present a method for DNA-free genome editing via the direct delivery of RNPs to canola mesophyll protoplasts. This method allows high-throughput in vivo testing of the efficacy of gRNA design as part of the transformation process to facilitate the selection of optimal designs prior to the generation of edited events. Of the 525 shoots regenerated via tissue culture from RNP-transfected protoplasts and screened for the presence of mutations in the targeted gene, 62% had one or more mutated target alleles and 50% had biallelic mutations at both targeted loci. This high editing efficiency compares favourably with similar CRISPR-Cas9 approaches used in other crop plants.